Effect of postural changes on cardiovascular parameters across gender. Issue 28 (July 2016) - Patel, Kieran; Rössler, Andreas; Lackner, Helmut Karl; Trozic, Irhad; Laing, Charles; Lorr, David; Green, David A; Hinghofer-Szalkay, Helmut; Goswami, Nandu
Abstract: Introduction: We investigated the effect of postural changes on various cardiovascular parameters across gender. Twenty-eight healthy subjects (16 male, 12 female) were observed at rest (supine) and subjected to 3 interventions; head-down tilt (HDT), HDT with lower body negative pressure (HDT+ LBNP at −30 mm Hg), and head-up tilt (HUT), each for 10 minutes separated by a 10 minutes recovery period. Methods: Measurements were recorded for heart rate (HR), standard deviation of the normal-to-normal intervals, root mean square of successive differences between the normal-to-normal intervals, heart rate variability-low frequency (LFRRI ), heart rate variability-high frequency (HFRRI ), low frequency/high frequency ratio (LFRRI /HFRRI ), systolic blood pressure (SBP), mean arterial pressure (MAP), diastolic blood pressure (DBP), total peripheral resistance index (TPRI), stroke index (SI), cardiac index (CI), index of contractility (IC), left ventricular work index, and left ventricular ejection time. Results: Across all cardiovascular parameters, there was a significant main effect of the intervention applied but there was no significant main effect of gender across all parameters. Conclusions: The results suggest that there are no specific gender differences in regards to the measured variables under the conditions of this study. Furthermore, these results suggest that in healthy subjects, there appears to be evidence that LBNP partially elicits similar cardiovascular responses to HUT, which supports the use of LBNP as an intervention to counteract the effects of central hypovolemia.